2014
DOI: 10.1007/s00772-014-1348-4
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm screening program in Poland

Abstract: BackgroundScreening for abdominal aortic aneurysms (AAA) is currently recommended by several vascular societies. In countries where it has been introduced the prevalence of AAAs differed greatly and was mainly related to cigarette smoking. The screening program also had an enormous impact on the decrease of AAA ruptures and reduced mortality rate. These facts have led to the introduction of the first screening program for AAAs in Poland.ObjectiveThe aim of the study was to determine the prevalence of AAAs amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…However, in this study, the prevalence of smoking cigarettes -one of the main risk factor of AAA -was also very high (55%). The distribution of the detected AAAs according to the maximum diameter was similar to the one observed in our study [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in this study, the prevalence of smoking cigarettes -one of the main risk factor of AAA -was also very high (55%). The distribution of the detected AAAs according to the maximum diameter was similar to the one observed in our study [23].…”
Section: Discussionsupporting
confidence: 89%
“…A similar study, held in Poland from 2009 to 2011 in the Kuyavian-Pomeranian Province by Jawien et al [23] showed that the prevalence of AAA in the population of men aged 60 years and older was 6.0%, which is higher than in our study. However, in this study, the prevalence of smoking cigarettes -one of the main risk factor of AAA -was also very high (55%).…”
Section: Discussioncontrasting
confidence: 48%
“…According to these guidelines, mortality from AAA can be reduced by almost a half within four years, mostly by reducing the incidence of ruptured aneurysms due to population screening for AAA of older men, in areas where the prevalence is 4% or more (level of evidence 1a, strength of recommendation A). In two studies conducted in the Kuyavian-Pomeranian voivodship in 2012 and 2013, AAA during screening among men aged 65 years and more was found in 5.4% of patients [17,18]. The data obtained in this study by the authors showed that the prevalence of AAA is a bit higher than the results obtained in the 1990s.…”
Section: Large Scale Population-based Studies Carried Out In the 1980smentioning
confidence: 48%
“…In those countries where screening campaigns are active, the mortality rate is in constant decline. The introduction of AAA screening saves lives, prevents the rupture risk, coincides with a falling prevalence of the disease, reduces the incidence of aneurysm rupture, decreases the mortality [1,9,18,34,36,40,57,66,67].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Also hypertension, CAD and family history of AAA are risk factors for AAA, but, it is important to underline family history should be considered with caution because the confidence interval is wide enough, therefore effect size pooled could be influenced. As regard to the role of hypertension as potential risk factor for AAA same authors [8,36,43,59,68] are in disagreement. Alcorn et al [56] suggest that individuals with hypertension are more likely to be evaluated clinically for the identification of AAA and this leads to a greater number of AAA diagnoses.…”
Section: Meta-analysismentioning
confidence: 99%